Uirassubrillia beckeri gen. n., sp. n. (Diptera: Chironomidae, Orthocladiinae) from northeastern Brazil - Mendes, Humberto Fonseca; Andersen, Trond; Pinho, Luiz Carlos (Zootaxa, 2013)
Uirassubrillia beckeri gen. n., sp. n. is described and illustrated based on male and female imagines from Bahia State in Brazil. The new genus is placed in the Brillia-group as the adults have a strongly setose body and setose wing membrane, RM is long and oblique, and the eye has a long, parallel-sided dorsomedian extension. The male hypopygium has a characteristic digitiform superior volsella and a bifurcate gonostylus. The female has three seminal capsules, two large and a third, smaller one.